Islamic Banks and the European Banking Union: An Overview of Critical Issues and Perspectives - Antoniazzi, Sandra (European Journal of Islamic Finance, 2022)
The aim of the paper is to provide a general, but in-depth, an overview of aspects of incompatibility and actual interest profiles of Islamic finance in relation to the legal system of the European Banking Union, identifying some prospects for positive future developments. It examines the relevant Islamic principles for banking and the differences from conventional European banks for regulation and supervision, some experiences and possible relationships. The modern communication between the Islamic banking scheme and the European (and international) one is certainly allowed by the activity of the IFSB regulator, especially about the adaptation to the Basel Committee standards and the related capital requirements, transparency criteria, common reference, considering the global application to operate in the international markets. The examination of the relationship with the European Banking Union allows the identification of future profiles of debate and research in Economics Law, considering the opportunity for regulatory adjustments and the interaction between EU and national law and the interesting ethical aims of the socially responsible Islamic finance.